2012
DOI: 10.1038/ki.2012.267
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptors mediate increased distal nephron acidification caused by acid retention

Abstract: Patients with a moderately reduced glomerular filtration rate (GFR) typically have no metabolic acidosis and a urine net acid excretion comparable to those with normal GFR, supporting greater per nephron acidification with moderately reduced GFR. We modeled such patients using rats with a surgical reduction of 2/3 kidney mass, yielding animals with reduced GFR without metabolic acidosis. We then tested the hypothesis that reduction of nephron mass augments distal nephron acidification in remnant nephrons media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 48 publications
1
66
0
1
Order By: Relevance
“…Although some observations pointed to a beneficial effect of acidosis in experimental renal disease in rodents, 28,32,33 the bulk of observations indicate that alkali treatment has beneficial and acidosis exacerbatory effects in experimental CKD. [34][35][36][37] Moreover, clinical studies in humans demonstrate that acidosis accelerates and alkali treatment retards the progression of CKD. 34,39,[74][75][76] Along those lines, decreased bicarbonate concentrations are associated with decline of eGFR in community-living older persons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some observations pointed to a beneficial effect of acidosis in experimental renal disease in rodents, 28,32,33 the bulk of observations indicate that alkali treatment has beneficial and acidosis exacerbatory effects in experimental CKD. [34][35][36][37] Moreover, clinical studies in humans demonstrate that acidosis accelerates and alkali treatment retards the progression of CKD. 34,39,[74][75][76] Along those lines, decreased bicarbonate concentrations are associated with decline of eGFR in community-living older persons.…”
Section: Discussionmentioning
confidence: 99%
“…38 Moreover, administration of alkali retards the progression of CKD in rodents. [34][35][36][37] In humans with CKD, acidosis is associated with worse kidney function, whereas the administration of bicarbonate, as shown in several studies, is associated with the slowing of progressive kidney disease. 37,39 Acidosis can be induced by dietary NH 4 Cl.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, MA was found to activate a series of regulatory mechanisms to compensate for disordered acid-base balance, including complement activation, 30 endothelin production, and activation of the renin-angiotensin system. [31][32][33] This subsequently induced additional kidney damage. However, in contrast with clinical consequences such as the development of a catabolic state, 34 development or exacerbation of bone disease, 35 and deterioration of kidney function, 36 the decisive mechanism by which MA induces cellular dysfunction was largely unknown.…”
Section: Discussionmentioning
confidence: 99%